2020
DOI: 10.4039/tce.2019.75
|View full text |Cite
|
Sign up to set email alerts
|

Cyclamen mite (Acari: Tarsonemidae) monitoring in eastern Canada strawberry (Rosaceae) fields and its potential control by the predatory miteNeoseiulus cucumeris(Acari: Phytoseiidae)

Abstract: The cyclamen mite (Phytonemus pallidus Banks; Acari: Tarsonemidae) has recently become a more important pest in Canadian strawberry (Fragaria × ananassa Duchesne ex Rozier; Rosaceae) production with the withdrawal of the pesticide endosulfan in 2016, yet its phenology under field conditions in Canada is poorly known. Moreover, while its biological control with predatory mites has shown potential, the effectiveness of this method has never been investigated under eastern Canadian field conditions. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…High densities may prevent fruit from being produced entirely [ 28 , 37 ]. Adults can overwinter in the crown of strawberry but in warmer climates they can continue to reproduce through the winter and females are capable of parthenogenesis [ 38 , 39 ].…”
Section: Strawberry Pests and Their Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…High densities may prevent fruit from being produced entirely [ 28 , 37 ]. Adults can overwinter in the crown of strawberry but in warmer climates they can continue to reproduce through the winter and females are capable of parthenogenesis [ 38 , 39 ].…”
Section: Strawberry Pests and Their Managementmentioning
confidence: 99%
“…Research conducted using hot water treatments found that soaking P.-pallidus -infested strawberry runners at 46 °C for 6.5 min killed P. pallidus [ 40 ]. Moreover, commercially available generalist phytoseiid mites such as Neoseiulus californicus McGregor and Neoseiulus cucumeris Oudemans have been shown to control phytophagous mites on strawberry [ 28 , 39 ]. For the management of P. pallidus in strawberry, prevention of pest infestation and pest establishment is a better tactic than crop rescue, owing to limited miticide compounds available and lack of effective pest suppression.…”
Section: Strawberry Pests and Their Managementmentioning
confidence: 99%
“…Development times are temperature-dependent (Easterbrook et al 2003), but cyclamen mite numbers increased from 50 eggs to 300-600 individuals, depending on strawberry cultivar, in 30 days at 20 °C (Rostami et al 2018). In the field, populations increased steadily from early spring to late summer and then gradually decreased until late fall (Patenaude et al 2020). Control decisions can be difficult due to the small size and cryptic lifestyle of cyclamen mite but also because factors affecting its distribution and spread in strawberry fields are not well known.…”
Section: Introductionmentioning
confidence: 99%
“…Before its phase-out, which began in 2016 in Canada and the United States of America, endosulfan was relied on in strawberry nurseries for cyclamen mite control and production of clean planting material. In recent years, cyclamen mite has become common in Ontario and Québec, Canada (Erica Pate, personal communication; Patenaude et al 2020), and abamectin (Agri-Mek® SC) is the only registered acaricide for cyclamen mite in strawberry in Canada (Ontario Ministry of Agriculture, Food and Rural Affairs 2021). Abamectin is usually applied once in mid-summer after field renovation in perennial short-day strawberry cultivars grown in matted-row, open-field systems.…”
Section: Introductionmentioning
confidence: 99%
“…In southern Minas Gerais, strawberry artrhopod pests attacked by predatory mites are mostly the two-spotted spider mite (Tetranychus urticae Koch, Tetranychidae), as well as the western flower thrips (Frankliniella occidentalis (Pergande), Thripidae). In other regions, also other mite species, as well as nematodes are important pests of this crop Patenaude et al 2020).…”
Section: Introductionmentioning
confidence: 99%